Like other children, they are also children. Societal ostracism of children with disability: A critical ethnography of service to children with disability, their parents and monitors of a psycho-medical school in Mali - Cheick Amadou Tidiane Ouattara; Ekene Francis Okagbue; Muhammad Yasir Ali; Amina A. Juma; Otto James Alfred Loum (Cogent Education, 2023)
AbstractSocietal ostracism and socio-cultural integration of children with disability, as well as parents’ and monitors’ challenges therefrom, constitute issues that deserve particular examination and consideration. Owing to that, through a qualitative ethnography, we investigated such issues employing in-depth interview and observation (n = 15). Some major findings are the following. Societal ostracism is a deeply-rooted social tendency of the mainstream in Mali that unobtrusively affects minority groups, especially children with disability. Due to that situation, if children with disability may end up wandering in streets and the consequences this entails, parents and monitors daily experience frustration, bewilderment, and disarray. Increased advocacy and sensitization by key actors would be an effective engine for driving socially paradigmatic change regarding the phenomena of societal ostracism and socio-cultural integration of children with disability. We also found out that preparing children with disability for socio-cultural life integration is as important as preparing society itself to welcome and receive these children. Parents and monitors need increased multifaceted support from government, social services, and relevant organizations to overcome difficulties and issues related to children’s disability and their socio-cultural integration.